PENGARUH KINERJA KEUANGAN DAN MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BEI 2021-2023 - Nahariyah Binti Irwan; Miftahol Horri (Jurnal Ilmiah Akuntansi, 2025)
This study aims to examine the effect of financial performance and earnings management practices on firm value in manufacturing companies in the infrastructure sector listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. Financial performance is measured using the Return on Assets (ROA) ratio, while earnings management is analyzed using Price to Book Value (PBV). This study uses a quantitative approach with multiple linear regression. The study population includes all infrastructure companies listed on the IDX, with samples drawn using a purposive sampling technique. The data used are secondary data from the companies' annual financial reports. The results show that simultaneously, financial performance and earnings management do not have a significant effect on firm value. Partially, financial performance also has no significant effect, while earnings management has been shown to have a significant effect on firm value. These findings indicate that investors pay more attention to earnings management practices than profitability indicators when assessing companies in the infrastructure sector. This research is expected to enrich the accounting literature and provide practical information for investors, managers, and regulators regarding the factors that influence firm value.